(untitled) (Eurasian Journal of Philology Science and Education, 2015)
In article methods of training in adequate use in written and oral speech of substantivized participles by pupils of the 7th classes of comprehensive schools of Kazakhstan with the training Russian, applied in the textbook "Russian" (Almaty: Atamura, 2012). The training material about substantivation process – transition of participles to a class of nouns – contains the tasks of different levels promoting development of skills and ability to carry out as the linguistic analysis of texts from the classical Russian and the Kazakh literature, comparing different syntactic functions of participles, and it is correct to use them in oral speech. Conclusions: similar approach to training of morphology of modern Russian promotes formation and development not only language and linguistic, but also communicative and others competences of the school students studying Russian as native.